Efficient very large scale integration power - Tan, S.X.-D (IEEE Transactions on computer-aided design of integrated circuits and systems)
We present an efficient method of minimizing the area of power/ground (P/G) networks in integrated circuit layouts subject to reliability constraints. Instead of directly sizing the original P/G network extracted from a circuit layout, as done previously, the new method first constructs a reduced but electrically equivalent P/G network. Then the sequence of linear programming method is applied to optimize the reduced network. The solution of the original network is then backsolved from the optimized reduced network. The new method exploits the regularities in the P/G networks to reduce the complexities of P/G networks. Experimental results show that the sizes of reduced networks are typically significantly smaller than that of the original networks. The resulting algorithm is fast enough that P/G networks with more than one million branches can be sized in a few minutes on modern Sun workstations.